2022
DOI: 10.3390/foods11213335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary L-malic Acid Supplementation on Meat Quality, Antioxidant Capacity and Muscle Fiber Characteristics of Finishing Pigs

Abstract: L-malic acid is a vital intermediate in the citric acid cycle and has been reported to improve the antioxidant capacity and aerobic oxidation of weaned piglets; however, its application in finishing pigs is limited at present. This study explored the effects of dietary L-malic acid supplementation on the carcass traits and meat quality of finishing pigs. In a 45-day experiment, 192 Duroc × Landrace × Yorkshire pigs (75.01 ± 0.51 kg) were divided into four treatments, i.e., a basal diet supplemented with 0, 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The BFMA was an unrefined malic acid product designed for the feed additive, the middle product during the production of pure malic acid from the fermentation products. The BFMA contained 20% L-malic acid and 80% carrier (1% bacterial protein, 2% polysaccharide, 2% fermentation residue, and 75% zeolite powder) [ 26 ]. The carrier was used in the present study to balance the dose of BFMA among experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…The BFMA was an unrefined malic acid product designed for the feed additive, the middle product during the production of pure malic acid from the fermentation products. The BFMA contained 20% L-malic acid and 80% carrier (1% bacterial protein, 2% polysaccharide, 2% fermentation residue, and 75% zeolite powder) [ 26 ]. The carrier was used in the present study to balance the dose of BFMA among experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…These clues indicated that the energy metabolism may be more active in the pectoral muscle of group G. Malate, the intermediate of the tricarboxylic acid (TCA) cycle, which was also higher in the pectoral muscle of group G. Bio-fermented malic acid supplemented in meal affected the water-holding capacity of breast muscle of broilers [ 34 ]. In pigs, a diet supplemented with L-malic acid could improve the meat color and carcass traits of finishing pigs [ 35 ]. The higher content of malate found in group G may affect the meat quality of the pectoral muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Yaks are the third largest breed of cattle in China, accounting for over 95% of the world’s yak population [ 1 ]. Studies indicate that fat content, particularly intramuscular fat (IMF) content, plays a significant role in the tenderness, juiciness, and flavor of meat [ 2 , 3 ]. However, the low IMF content of yak meat has become a major bottleneck, restricting high-quality meat development in the yak industry.…”
Section: Introductionmentioning
confidence: 99%